2018
DOI: 10.1039/c7ra12865g
|View full text |Cite
|
Sign up to set email alerts
|

Flame-retardant effect and mechanism of melamine phosphate on silicone thermoplastic elastomer

Abstract: Halogen-free flame retardant – MP was successfully adopted to improve the comprehensive properties of the novel Si-TPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Melamine had among the fewest red indicators, having only four, in addition to one orange, five yellow, and the highest number of green indicators (10). Melamine is often used together with OPFRs, , but has also been reported to have good flame retardancy itself. , PBDPP (four red, three orange, five yellow, and eight green indicators) appeared to be the best OPFR as well as the second best choice among all studied chemicals. The BFRs that appear as best alternatives are BEH-TEBP (five red, three orange, five yellow, and seven green indicators) and BPA-BDPP (five red, four orange, four yellow, and seven green indicators).…”
Section: Results and Discussionmentioning
confidence: 92%
“…Melamine had among the fewest red indicators, having only four, in addition to one orange, five yellow, and the highest number of green indicators (10). Melamine is often used together with OPFRs, , but has also been reported to have good flame retardancy itself. , PBDPP (four red, three orange, five yellow, and eight green indicators) appeared to be the best OPFR as well as the second best choice among all studied chemicals. The BFRs that appear as best alternatives are BEH-TEBP (five red, three orange, five yellow, and seven green indicators) and BPA-BDPP (five red, four orange, four yellow, and seven green indicators).…”
Section: Results and Discussionmentioning
confidence: 92%
“…The compatibilizer improved the adhesion between the PLA and TPU phases, which was attributed to the fact that the anhydride ring of PP- g -MAH was opened and two carboxylic acid groups were formed by the action of the melt blending; one carboxylic acid group was esterified with the terminal hydroxyl group of PLA and the other carboxylic acid group was esterified with the end hydroxyl group of PLA. The other carboxylic acid group is attached to the carbamate in TPU to form a branched structure, forming a network structure in situ at the interface [ 22 , 23 , 24 , 25 ]. As can be observed in Figure 2 d,e, the fracture surface becomes rough and ridged, and there is significant delamination in the direction of the fracture, showing a folded, ductile fracture feature [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure 4(a), it can be observed that the addition of NSH in SR composite leads to relatively low tensile strength. This may be due to the excessive water released by NSH filler decomposition cause the local vulcanization of silicone rubber, on the other hand, the large size of NSH particles can appear aggregation, resulting in the worse dispersion of NSH in silicone rubber matrix, thus the decrease of the tensile strength 27 . When the addition of EG for the SR composite, the tensile strength somewhat decreases compared to the other composites, resulting from the large average particle size of EG which weakens the interaction and leads to the stress concentration.…”
Section: Resultsmentioning
confidence: 99%